Improving Elementary School Students' Knowledge About the Dangers of Intestinal Worms Through Interactive Health Education Programs: Peningkatan Kesadaran Siswa SD Tentang Bahaya Cacing Usus melalui Program Edukasi Kesehatan Interaktif - Syahida Ariyanti; Nurfitri Nurfitri; Arsyik Ibrahim (B-Creta Publisher, 2026)
Helminthiasis is a disease commonly found in tropical regions, transmitted through soil, and capable of causing intestinal tract infections that result in the loss of carbohydrates, proteins, and blood. This disease is generally associated with poor personal hygiene. The prevalence of helminthiasis in Indonesia ranges from 2.5% to 62%, with an average prevalence of 28% across 181 districts/cities in 2021 (Ministry of Health, 2017). This health promotion activity aimed to improve the knowledge and awareness of students at SD Muhammadiyah 4 Samarinda regarding the dangers and prevention of helminthiasis, as well as to provide understanding of the pharmacist’s role in community life. The methods included presentations using PowerPoint, distribution of leaflets, and administration of pre- and post-intervention questionnaires. The results showed an 8% increase in students’ knowledge about helminthiasis prevention, rising from 81% before the intervention to 89% after.